2012
DOI: 10.1103/physreve.85.026213
|View full text |Cite
|
Sign up to set email alerts
|

Control of turbulence in heterogeneous excitable media

Abstract: Control of turbulence in two kinds of typical heterogeneous excitable media by applying a combined method is investigated. It is found that local-low-amplitude and high-frequency pacing (LHP) is effective to suppress turbulence if the deviation of the heterogeneity is minor. However, LHP is invalid when the deviation is large. Studies show that an additional radial electric field can greatly increase the efficiency of LHP. The underlying mechanisms of successful control in the two kinds of cases are different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…(5)- (7). When r>r c , the arms in multi-armed dense spirals will rotate independently just like 1-armed dense spiral.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…(5)- (7). When r>r c , the arms in multi-armed dense spirals will rotate independently just like 1-armed dense spiral.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…It was confirmed that optimized noise on network can be active to develop a spiral wave [40] due to coherence resonance [41] , [42] . More often, target wave can also be induced in the media due to heterogeneity [43] and the emitting wave can be used to suppress the spiral wave and turbulence of the media [44] , for example, the tip dynamics of spiral wave is changed by the fractal heterogeneity [43] , and the heterogeneity by a rotating electric field [45] can emit ordered wave to regulate the behavior of excitable media.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of a spiral wave in a reaction-diffusion system has been investigated extensively, and it is confirmed that the formation of a spiral wave in cardiac tissue could be associated with specific types of arrhythmias (reentrant ventricular tachycardia and ventricular fibrillation) [26], [27]. Some reliable theoretical models [28][31] have been proposed to measure the dynamics of spiral waves, and some feasible schemes [32][36] have been presented to suppress the spiral wave turbulence, and to prevent the breakup [37] of spiral waves. Spiral waves and target waves [38][41] are ordered waves, and these waves are often observed in the excitable media.…”
Section: Introductionmentioning
confidence: 93%